Relationship between Serum 25-Hydroxyvitamin D and Lower Extremity Arterial Disease in Type 2 Diabetes Mellitus Patients and the Analysis of the Intervention of Vitamin D - Wan Zhou; Shan-Dong Ye (Journal of Diabetes Research)
The aim of this study was to explore the relationship between serum 25-hydroxyvitamin D [25(OH)D] concentrations and lower extremity arterial disease (LEAD) in type 2 diabetes mellitus (T2DM) patients and to investigate the intervention effect of vitamin D. 145 subjects were assigned to a control group (Group NC), T2DM group (Group DM1), and T2DM complicated with LEAD group (Group DM2); then Group DM2 were randomly divided into Group DM3 who received oral hypoglycemic agents and Group DM4 who received oral hypoglycemic drugs and vitamin D3 therapy. Compared to Group NC, 25(OH)D was significantly lower in Group DM2 and marginally lower in Group DM1. In contrast to baseline and Group DM3, 25(OH)D rose while low density lipoprotein (LDL), retinol binding protein 4 (RBP4), and HbA1c significantly lowered in Group DM4. Statistical analysis revealed that 25(OH)D had a negative correlation with RBP4, duration, HbA1c, homeostasis model assessment for insulin resistance (HOMA-IR), and fasting plasma glucose (FPG). LDL, systolic blood pressure (SBP), FPG, and smoking were risk factors of LEAD while high density lipoprotein (HDL) and 25(OH)D were protective ones. Therefore, we deduced that low level of 25(OH)D is significantly associated with the occurrence of T2DM complicated with LEAD.